The role of relationships in improving early diagnosis of prostate cancer. (1st April 2011) - Forbat, L; Hubbard, G; Place, M; Boyd, K; Leung, H; Winslow, F; Kelly, D
Abstract : Abstract: Introduction: Early diagnosis is critical in reducing mortality in prostate cancer. The extant literature identifies a range of variables which impact on when men present in primary care. For example, recent evidence suggests that men from high deprivation areas are significantly more likely to present with advanced disease and have lower survival rates. Psychosocial theories provide a framework for understanding patterns in the timing of diagnoses, for example, the role of social context and relationships in help-seeking behaviour. Aim: To identify how men account for the timing of their presentation and subsequent diagnosis with advanced disease. Methods: Embedded mixed-method design involving a postal survey (N=320) and semi-structured interviews with a purposive sub-sample of men and partners (N=30). Analysis drew primarily on χ 2 and spearman's correlation, alongside framework analysis of the qualitative data, informed by Anderson's (1995) model of Total Patient Delay. Results: Data indicate that relationships and experiential knowledge play significant roles in gaining a diagnosis. Notably friends/relatives are key sources of information on prostate cancer and often prompt help-seeking behaviour. Indeed, men's perceptions of risk are not informed by clinical risk factors such as age and family history, but by their own and friends/relatives' experiential knowledge. Conclusion: Health promotion interventions should draw on relational theories, to be cognisant of the important role of relationships in help-seeking behaviour. Adopting a systemic approach has the potential to reach men at higher risk of prostate cancer and contribute to earlier diagnosis.